Self-selecting Fluid Intake while Maintaining High Carbohydrate Availability Does not Impair Half-marathon Performance - Lee, M. J. C.; Hammond, K. M.; Vasdev, A.; Poole, K. L.; Impey, S. G.; Close, G. L.; Morton, J. P. (International Journal of Sports Medicine, 2014)
We aimed to test the hypothesis that self-selecting fluid intake but maintaining high exogenous CHO availability (60 g/h) does not compromise half-marathon performance. 15 participants completed 3 half-marathons while drinking a 6% CHO solution to guidelines (DRINK) or a non-caloric solution in self-selected volumes when consuming 3×glucose (20 g) gels (G-GEL) or glucose-fructose (13 g glucose+7 g fructose) gels (GF-GEL) per hour. Fluid intake (DRINK: 1 557±182, G-GEL: 473±234, GF-GEL: 404±144 ml) and percent body mass loss (DRINK: − 0.8±0.9, G-GEL: − 2.0±0.6, GF-GEL: −2.3±1.1) were different (P<0.05) between conditions, though race time did not differ (DRINK: 110.6±14.4, G-GEL: 110.3±14.6, GF-GEL: 113.7±12.8 min). In G-GEL, there was a positive correlation (P<0.05) between body mass loss and race time. Plasma glucose was lower (P<0.05) in GF-GEL compared with other conditions, and total CHO oxidation (DRINK: 3.2±0.5, G-GEL: 3.0±0.4, GF-GEL: 2.6±0.4 g/min) was lower (P=0.06) in this trial. Self-selecting fluid intake but maintaining high CHO availability does not impair half-marathon performance. Additionally, consuming glucose-fructose mixtures in sub-optimal amounts reduces plasma glucose and total rates of CHO oxidation.
Keywords: glucose; fructose; dehydration; running; endurance